Thermomechanical performance of shape memory alloy spring by homogeneous distribution of temperature - Imran, Husam Yahya; Abang Abdul Majid, Dayang Laila; Abdul Hamid, Mohd Faisal; Abdullah, Ermira Junita; Mohammed, Saleem Ethaib; Karunakaran, Sivasanghari (The Aeronautical and Astronautical Society of the Republic of China, 2024)
In this paper, the thermomechanical characteristic behavior of a shape memory alloy (SMA) spring was studied. Under homogenous distribution of temperature by immersion in the hot and cold water, the thermal equilibrium of the SMA spring was obtained and its performance under different preloads applied was measured. The thermomechanical behaviors and properties of the SMA spring for one cycle were derived from the analysis of the displacement of contraction, pulling force produced and temperature versus response time through experimental tests. The experimental results showed that the performance of the SMA spring and the response time depend on the technique of the heating phase to activate it and the cooling phase to passivation it, as well as on the wire diameter and the preload applied. The maximum displacement contractions produced from 2.5 N and 1.5 N pulling forces for 0.51 mm and 0.38 mm wire diameter of the SMA spring were found as 49 mm and 35 mm respectively. The SMA spring was heated by increasing the temperature rate 0.3℃ H/s of water and the temperature was decreased by adding cold water at a rate -6.1℃/s. The response time of the SMA springs that occurred at the temperature 74℃ and 82℃ were respectively 37 s and 50 s. The experimental results for both contraction-temperature and force-time responses at different preload, as well as collection of contraction-force-temperature responses to response time provide a good visualization as references for the design dimensioning and fabrication of the SMA spring as actuator, sensor and heat engine.